The Impact Of Physical Training Programs On Basic Karate Skills Among Students at State Senior High School 14 Gowa - Silatul Rahmi; M. Imran Hasanuddin (Program Studi Pendidikan Jasmani Kesehatan dan Rekreasi, 2025)
This study aims to explore the impact of physical training programs on basic karate skills in SMA Negeri 14 Gowa students. Structured and intensive physical exercises are believed to improve motor skills and basic karate techniques, such as punches, kicks, balance, and agility. Using a quantitative approach with experimental design, this study involved students who participated in a karate physical training program over a specific period. Karate basic skills data were collected through skill tests before and after the training program (pre-test and post-test). The results showed a significant improvement in students' basic karate skills, with the difference in scores between pre-test and post-test ranging from 1.49 to 9.84 points. The biggest increase occurred in students who had high motivation in participating in the training program. These findings indicate that structured physical exercise contributes positively to improving basic karate technique skills, as well as improving body strength and balance. Nonetheless, the study also shows that the duration and frequency of limited exercises affect the extent to which skill improvement can be achieved. This research contributes to the development of karate training curricula in schools and provides practical insights for coaches and sports teachers in designing more effective training programs.